The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1063/1.4997048
|View full text |Cite
|
Sign up to set email alerts
|

Multiple exciton generation in chiral carbon nanotubes: Density functional theory based computation

Abstract: We use a Boltzmann transport equation (BE) to study time evolution of a photo-excited state in a nanoparticle including phonon-mediated exciton relaxation and the multiple exciton generation (MEG) processes, such as exciton-to-biexciton multiplication and biexciton-to-exciton recombination. BE collision integrals are computed using Kadanoff-Baym-Keldysh many-body perturbation theory based on density functional theory simulations, including exciton effects. We compute internal quantum efficiency (QE), which is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…For SWCNTs, the set of approximations stated above have been checked and shown to be reasonable by reproducing experimental results for the low-energy absorption peaks in (6,2), (6,5) and (10,5) SWCNTs within 5-13% error [14].…”
Section: A Microscopic Hamiltonianmentioning
confidence: 84%
See 4 more Smart Citations
“…For SWCNTs, the set of approximations stated above have been checked and shown to be reasonable by reproducing experimental results for the low-energy absorption peaks in (6,2), (6,5) and (10,5) SWCNTs within 5-13% error [14].…”
Section: A Microscopic Hamiltonianmentioning
confidence: 84%
“…So, here we perform calculations at the Γ point only. Previously, it has been shown that the variations in the single particle energies over the Brillouin zone is reasonably small (≈ 10%) when three unit cells have been included in the simulation instead of one [14]. For the (6,5) SWCNT only one unit cell was included due to high computational cost.…”
Section: Atomistic Modelsmentioning
confidence: 99%
See 3 more Smart Citations